Magnetisation transfer ratio in the normal appearing white matter predicts progression of disability over 1 year in early primary progressive multiple sclerosis - Khaleeli, Z (BMJ Group, 2007)
BACKGROUND: Progression rates in primary progressive multiple sclerosis (PPMS) vary widely and brain magnetisation transfer imaging (MTI) has potential as an early prognostic indicator. We investigated the predictive value of MTI and the longitudinal changes developing over 1 year in early PPMS. AIMS: To determine (1) whether baseline brain MTI parameters in early PPMS predict clinical changes over 1 year, independent of brain volume and (2) whether a change in magnetisation transfer (MT) parameters occurs over 1 year, independent of atrophy. METHODS: 30 patients with PPMS within 5 years of symptom onset and 15 controls underwent MT and volumetric imaging studies, at baseline and at 1 year. Patients underwent clinical assessment using the Expanded Disability Status Scale (EDSS) and Multiple Sclerosis Functional Composite (MSFC), including the timed walk subtest (TWT). Normalised MT histograms were generated for whole brain, normal appearing brain tissue (NABT) and normal appearing white and grey matter (NAWM and NAGM) segments. Multiple regression analyses were performed to investigate whether baseline MTR parameters predicted clinical change over 1 year, adjusting for baseline brain volume. MTR changes over 1 year were assessed using paired t tests. RESULTS: In patients, lower baseline NAWM MTR predicted greater deterioration in EDSS and MSFC, particularly in walking ability measured by the TWT, independent of NAWM baseline volume (p = 0.001). NAGM MTR mean (p<0.001), and to a lesser extent NAWM mean (p = 0.011) and lesion MTR (p = 0.03), decreased over 1 year. CONCLUSIONS: NAWM MTR may provide information on short term clinical prognosis in early PPMS. MTI is sensitive to brain tissue changes over 1 year in early PPMS, which were primarily seen in the NAGM.